Reconstruction Pastoral Ministry Concept of the Assemblies of God Church in North Sulawesi Indonesia - Alexander Stevanus (Sekolah Tinggi Agama Kristen Lentera Bangsa Manado, 2023)
Abstract: This study aims to determine the problems of pastoral care that occur in the Assemblies of God Church in North Sulawesi, Indonesia. Assemblies of God's efforts are reconstructing (providing a solution proposal) regarding pastoral care in an effort to develop the Assemblies of God congregation. To obtain research data, the authors used documents, both books and journals as a theoretical basis and conducted interviews with 14 church leaders as respondents/research subjects from regional organizational leaders, pastors and academics. The research was conducted using qualitative research methods by conducting interviews with 14 Assemblies of God leaders in North Sulawesi. Retrieval of research data using probability sampling with purposive sampling technique. The results showed that there were problems in Assemblies of God's pastoral care, especially with regard to pastoral care. The problem that occurs is the wrong paradigm regarding the concept of pastoral care in pastoral care caused by the old theoretical concept of pastoral care among church leaders, and the church's struggles in terms of independence. Therefore, in this study, two new theories were proposed in the form of proposed solutions, namely; 1) reconstruction of theological education (contextual pastoral care development), and 2) Striving for church independence. Keywords: reconstruction, pastoral care, church